FAULT DIAGNOSIS OF SUBTHRESHOLD LEAKAGE CURRENT DEFECTS IN DRAM (International Journal of Engineering Sciences & Management Research, 2016)
The minimum feature size of dynamic RAM has been down-scaled, so several studies have been carried out to determine ways to protect cell data from leakage current in many areas. Due to leakage sources, permanent error occurs. Many permanent faults are a result of manufacturing defects, which can be detected during manufacture testing. These errors can also occur at runtime. A self-contained adaptive system for detecting and bypassing permanent errors in on-chip interconnects is proposed. This system reroutes data on erroneous links to a set of spare wires without interrupting the data flow